The (in)significance of TB and COVID-19 co-infection. Issue 2 (20th August 2020) - Khurana, Alkesh Kumar; Aggarwal, Deepak
We read with great interest the research letter by Tadolini et al. [1], in which they have published the first cohort of 49 cases of tuberculosis (TB) and coronavirus disease 20019 (COVID-19) co-infection. However, a few issues regarding the letter need to be addressed. In the fight against COVID-19 pandemic, we should not forget to suspect and manage TB appropriately, as it is still one of the leading infectious causes of death worldwide https://bit.ly/30FZs9C